parody and women's discourse in Tahmineh's Story novel - Abdollah Hasanzadeh Mirali; Fatemeh Zamani (مطالعات زبانی و بلاغی)
One of the achievements of the Constitutional Revolution at various levels of society and consequently literary texts is to pay attention to women and discuss their issues and problems. for example, we can mention the works of Mohammad Mohammad Ali, in which women have a special position. he can try to show another voice (woman) that has been silenced in front of the dominant power and ideology of patriarchy by using the story of Rostam and Sohrab and recreating this story from Tahmineh's feminine point of view. This article is trying to answer the question that how the intertextual relations of this work with Shahnameh have led to polyphony and women's discourse in Tahmineh's story novel. Therefore, the article has shown the author's linguistic and sociological contradictions from the story of Rostam and Sohrab relying on the logic of Bakhtin's dialogue. the result of the issue has shown that the author in order to centralize the position of women in recreating the story of Shahnameh uses the features of women's discourse such as the color-word, women's perspective, women's words, women's emotions, and feelings, women's syntactic structure in sentences. Also, in the sociological contradiction of the Shahnameh narration, he has dealt with women's intellectual and financial independence, women's identity, struggle against women's being different, and so on.